Deformable unsaturated laterite soil under vibration impact with dissimilar moisture content. (May 2019) - Abd Rashid, MF.; Alias, N.; Ahmad, K.; Sa'ari, R.; Ramli, MZ.; Ibrahim, Z.
Abstract: Vibrations from vehicle traffic, machinery and operations from construction activities such as blasting are examples of some natural and man-made vibration phenomenon's that can cause dynamic stress when imposed onto soils. In order to ensure sustainability of the geo-environment, the impacts caused by these vibrations as well as the changes in moisture content needs to be addressed. To achieve this, the behaviour of vibrated deformable double-porosity under dissimilar moisture content in non-repeated vibration was assessed and characterized through laboratory experiments. Investigation of deformable unsaturated laterite soil by aggregating laterite soil using 29%, 30%, 32% and 34% moisture content was carried out and presented in this paper. An acrylic soil column, accelerometer and vibrating table were used to conduct the experiments. The acrylic columns were filled with each aggregated soil and the soil was then compressed to a height of 10 cm, which had been pre-determined beforehand. Accelerometers were installed to a vibrating table where each soil column was tested to measure the time histories of high-frequency acceleration on the surfaces of both the laterite soil and vibrating table. Acceleration was observed at two points, namely; (1) the surface of the soil sample and (2) the surface of the vibrating table. The amplitude of the vibrating table was increased in order to test for repeated vibration. Maximum amplitudes were recorded by collecting the acceleration time histories and the amplitude of displacement was increased in order to carry out the tests. The outcome of the tests demonstrated that there was an increase of the acceleration response in non-repeated vibration when moisture contents were also increased. For the vibrated samples that were used, it was found that there was a rearrangement of the soils structure and as expected, the porosity characteristics that were identified had influenced the liquid penetrations' speed.